Pengaruh Profitabilitas, Likuiditas, Leverage dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Gustiana Putri Novaliza; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of profitability, liquidity, leverage and company size on company value. The object of this research is food and beverage sector companies listed on the IDX in 2019-2023. This research used a quantitative approach. The sampling method used was purposive sampling and 25 companies were obtained so that there were 104 samples in accordance with the criteria. The data used is secondary data obtained from the company's annual report. The data analysis method used multiple linear regression analysis. The research results show that profitability and liquidity have an effect on company value, while leverage and company size have no effect on company value.